2022
DOI: 10.2196/33262
|View full text |Cite
|
Sign up to set email alerts
|

Self-reliance, Social Norms, and Self-stigma as Barriers to Psychosocial Help-Seeking Among Rural Cancer Survivors With Cancer-Related Distress: Qualitative Interview Study

Abstract: Background Even when technology allows rural cancer survivors to connect with supportive care providers from a distance, uptake of psychosocial referrals is low. Fewer than one-third of participants in a telemedicine intervention for identifying rural survivors with high distress and connecting them with care accepted psychosocial referral. Objective The purpose of this research was to examine the reasons for which rural cancer survivors did not accept … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 60 publications
(81 reference statements)
1
16
0
Order By: Relevance
“…Notably, in that study, it was more common for RCS than NRCS to report the belief that they needed to handle their cancer experience by themselves to protect their family from worrying. Similarly, a recent qualitative study identified self‐reliance as a strategy for coping with cancer among rural patients 48 . Notably, many of the reported social constraint experiences in this study were unintentional and resulted from a network that in most cases tried to be supportive but did not do so in a way that CS wanted.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Notably, in that study, it was more common for RCS than NRCS to report the belief that they needed to handle their cancer experience by themselves to protect their family from worrying. Similarly, a recent qualitative study identified self‐reliance as a strategy for coping with cancer among rural patients 48 . Notably, many of the reported social constraint experiences in this study were unintentional and resulted from a network that in most cases tried to be supportive but did not do so in a way that CS wanted.…”
Section: Discussionmentioning
confidence: 61%
“…Similarly, a recent qualitative study identified self-reliance as a strategy for coping with cancer among rural patients. 48 Notably, many of the reported social constraint experiences in this study were unintentional and resulted from a network that in most cases tried to be supportive but did not do so in a way that CS wanted. Cancer-related communication can be challenging, and negative social experiences can hinder CS' ability to emotionally and cognitively process their cancer experience.…”
Section: Discussionmentioning
confidence: 89%
“…Self-reliance, as a construct, is related to hardiness, independence, resilience and individualism (Bacsu et al, 2017;Bernacchi et al, 2021;Collins et al 2009, Keller & Owens, Online Journal of Rural Nursing and Health Care, 22(2) https://doi.org/10.14574/ojrnhc.v22i2.716 70 2020; Kuntz et al, 2018;Wagnild & Torma, 2018). Numerous studies have explored the concept of self-reliance in rural communities and have identified it as one of the factors that contributes to the differences in health seeking behaviors between rural and urban populations (DeGuzman et al, 2022;Starcher et al, 2017), particularly mental health seeking behaviors (Fennell et al, 2018).…”
Section: Defining Attributesmentioning
confidence: 99%
“…Further complicating rural survivorship care, providers report perceiving rural culture to be a barrier to providing health services, and many existing interventions may not be tailored to rural communities (Farmer et al., 2012). For example, rural values of autonomy and independence can influence survivors’ decisions to accept or decline health interventions (Carnahan et al., 2021; DeGuzman et al., 2022). In fact, rural survivors may prefer to seek care from informal family caregivers and community networks instead of healthcare providers (Bernacchi et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…One way to improve QoL while addressing multilevel social and environmental impacts is through interventions that use a strengths‐based approach (DeGuzman et al., 2022) to promote resilience , or the ability to adapt positively when faced with challenges (Fleming & Ledogar, 2008). Previous research suggests rural cancer survivors strengthen resilience through their rural community networks, and that interventions targeting resilience should be embedded within the community and tailored to rural culture and context (Bernacchi et al., 2021; Rogers‐Clark, 2002).…”
Section: Introductionmentioning
confidence: 99%